Fluid signal changes around the knee on MRI are associated with increased volumes of subcutaneous fat: a case-control study. Issue 1 (December 2016) - Trevor, Gaunt; Carey, Frank; Cahir, John; Toms, Andoni
Abstract Background Fluid in the subcutaneous fat is a common finding anterior to the knee on MRI. This may be caused by chronic low-grade shearing injuries in patients who are overweight. The purpose of this study was to determine if there is a difference in the amount of subcutaneous fat around the knee between patients with these appearances and controls. Methods This was a retrospective case-control study. Following a sample size calculation on pilot data, eighteen sequential patients demonstrating hyper-intense subcutaneous signal changes around the knee on fat-saturated T2-weighted MRI were identified from PACS (18 females, mean age 45, range 31–62). Age and gender-matched patients without abnormal T2 MR signal changes were selected. Two observers independently drew regions of interest representing cross-sectional areas of bone and fat. The location of T2 signal hyper-intense lesions was characterized by consensus. Results Inter and intra-rater intraclass reproducibility was "excellent" (ICC > 0.8). The mean cross-sectional area of bone for patients with T2 hyper-intense lesions was 31.79cm2 (SD 2.57) and for controls 30.11cm2 (SD 3.20) which was not significantly different (p = 0.09). The median cross-sectional area of fat for the study group was 62.29cm2 (IQR 57.1–66.5) and for controls was 32.77cm2 (IQR 24.8–32.3) which was significantly different (p < 0.0001). Consensus agreement demonstrated all T2 hyper-intense lesions were anterior to the knee extensor mechanism. Conclusion Subcutaneous fluid around the knee is associated with an increased amount of subcutaneous fat, anterior to the knee extensor mechanism. This may be caused by shearing injuries in fat with reduced elasticity associated with metabolic syndrome.